EFFORTS BY THE DEPARTMENT OF COMMUNICATIONS, INFORMATICS AND STATISTICS (DISKOMINSTA) TO SUPPORT SUPERVISION OF CHILDREN AND ADOLESCENTS IN THE USE OF SOCIAL MEDIA IN BARRU REGENCY - Nurlia Nurlia; Samsibar Samsibar (Jurnal Scientia, 2023)
This research aims to determine the efforts of the Department of Communication, Informatics and Statistics (DISKOMINSTA) to support the supervision of children and adolescents in the use of social media in Barru Regency. The type of research uses descriptive qualitative, the type of data used is primary and secondary data accompanied by data collection techniques used applied, namely observation, interviews and documentation, while data analysis techniques go through the stages of data collection, data reduction, data presentation, and drawing conclusions or verification. The results show that the efforts of the Department of Communications, Informatics and Statistics (DISKOMINSTA) to support the supervision of children and adolescents in media use Social Affairs in Barru Regency, formed a KIM (community informant group) which went directly into the field to carry out supervision, one of which was monitoring opinion aspirations that were conveyed to youth and teenagers, because not all people understand good communication techniques in public, sometimes what they see different from what he said, the problem that was found was then processed and then forwarded to the relevant agencies.